2021
DOI: 10.3389/fenrg.2021.765817
|View full text |Cite
|
Sign up to set email alerts
|

Can Prosuming Become Perilous? Exploring Systems of Control and Domestic Abuse in the Smart Homes of the Future

Abstract: In what ways can new, emerging digital technologies and energy business models such as “prosuming” become intertwined with troubling patterns of domestic abuse and violence? Domestic violence entails controlling, coercive or threatening behaviours, to gain or maintain power and control between intimate partners or family members regardless of gender or sexuality. The rapid development of digital communication services, smart homes, and digitalization processes such as prosuming create surprising threats relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…This research has identified that men are more likely to do the work involved in setting up, maintaining, using or responding to technologies in the home, which can take them away from other, more traditional, household tasks (Aagaard 2022;Kennedy et al 2015;Rode & Poole 2018;Strengers & Nicholls 2018). Relatedly, a smaller body of research is exploring the gendered effects of increasing automation, Internet of Things and smart devices in the home, such as the increasing surveillance and manipulation (Sadowski et al 2021) and the potential inclusion of these technologies in digital abuse and domestic violence (Lopez-Neira et al 2019;Sovacool et al 2021;Strengers et al 2019;Strengers & Kennedy 2020;Tanczer et al 2021). In the context of energy ambitions for smart technology, several studies have noted men's heightened interest; however, few studies have explored the gendered labour involved in achieving energy flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…This research has identified that men are more likely to do the work involved in setting up, maintaining, using or responding to technologies in the home, which can take them away from other, more traditional, household tasks (Aagaard 2022;Kennedy et al 2015;Rode & Poole 2018;Strengers & Nicholls 2018). Relatedly, a smaller body of research is exploring the gendered effects of increasing automation, Internet of Things and smart devices in the home, such as the increasing surveillance and manipulation (Sadowski et al 2021) and the potential inclusion of these technologies in digital abuse and domestic violence (Lopez-Neira et al 2019;Sovacool et al 2021;Strengers et al 2019;Strengers & Kennedy 2020;Tanczer et al 2021). In the context of energy ambitions for smart technology, several studies have noted men's heightened interest; however, few studies have explored the gendered labour involved in achieving energy flexibility.…”
Section: Introductionmentioning
confidence: 99%